An Archaeology of Australia Since 1788 - Lawrence, Susan. author. aut Link
XIX, 421 p. 87 illus.
Keywords: This volume provides an important new synthesis of archaeological work carried out in Australia on the post-contact period. It draws on dozens of case studies from a wide geographical and temporal span to explore the daily life of Australians in settings such as convict stations, goldfields, whalers' camps, farms, pastoral estates and urban neighbourhoods. The different conditions experienced by various groups of people are described in detail, including rich and poor, convicts and their superiors, Aboriginal people, women, children, and migrant groups. The social themes of gender, class, ethnicity, status and identity inform every chapter, demonstrating that these are vital parts of human experience, and cannot be separated from archaeologies of industry, urbanization and culture contact. The book engages with a wide range of contemporary discussions and debates within Australian history and the international discipline of historical archaeology. The colonization of Australia was part of the international expansion of European hegemony in the eighteenth and nineteenth century. The material discussed here is thus fundamentally part of the global processes of colonization and the creation of settler societies, the industrial revolution, the development of mass consumer culture, and the emergence of national identities. Drawing out these themes and integrating them with the analysis of archaeological materials highlights the vital relevance of archaeology in modern society.